The World Health Organization’s Mental Health and Substance Abuse Programme - Saraceno, Benedetto (Int Psychiatry, 2004)
There has been a rapid rise in the number of people with mental disorders. These disorders represent a major challenge to global development. The burden will be higher in developing countries, which have the least resources to respond. World-wide, 450 million people are affected at any given time. No group is immune to mental disorders but the risk is higher among: the poor; children and adolescents; abused women; the unemployed; persons with little education; neglected elderly people; victims of violence; migrants and refugees; and indigenous populations.